Caffeine potentiates cocaine-induced testicular toxicity in mice: evidence of psychostimulant-mediated effects on the local dopaminergic system - Gonzalez, Candela Rocio (2015)
Several organ systems can be affected by psychostimulant toxicity. However, there is not sufficient evidence about the impact of psychostimulant intake on testicular physiology and catecholaminergic systems. The aim of the present study was to further explore potential toxic consequences of chronic exposure to cocaine, caffeine, and their combination on testicular physiology. Mice were injected with a 13-day chronic binge regimen of caffeine (3x5mg/kg), cocaine (3×10mg/kg), or combined administration. Mice treated with cocaine alone or combined with caffeine showed reduced volume of the seminiferous tubule associated to a reduction in the number of spermatogonia. Cocaine-only and combined treatments induced increased lipid peroxidation evaluated by TBARS assay and decreased glutathione peroxidase mRNA expression. Importantly, caffeine-cocaine combination potentiated the cocaine-induced germ cell loss, and induced pro-apoptotic BAX protein expression and diminished adenosine receptor A1 mRNA levels. We analyzed markers of dopaminergic function in the testis and detected the presence of tyrosine hydroxylase (TH) in the cytoplasm of androgen-producing Leydig cells, but also in meiotic germs cells within seminiferous tubules. Moreover, using transgenic BAC-Drd1a-tdTomato and D2R-eGFP mice, we report for the first time the presence of dopamine receptors (DRs) D1 and D2 in testicular mouse Leydig cells. Interestingly, the presence of DRD1 was also detected in the spermatogonia nearest the basal lamina of the seminiferous tubules, which did not show TH staining. We observed that psychostimulants induced downregulation of DRs mRNA expression and upregulation of TH protein expression in the testis. These findings suggest a potential role of the local dopaminergic system in psychostimulant-induced testicular pathology.